Improving Grammar Mastery by Using Scramble Method of the Eleventh-Grade Students at Senior High School Number 2 Palopo - Andi Hasriani; Masruddin (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research focused on using the scrambling method to teach grammar at the eleventh-grade students of Senior High School Number 2 Palopo. The research problem of this research was: “Does the scrambling method effectively improve students’ grammar mastery?”. The objective of this research was to find out whether or not the scrambling method effectively improves students’ grammar mastery. In this research, the researcher used pre-experimental design, and the treatments were conducted in six meetings. The population of this research was the eleventh-grade students of senior high school 2 Palopo. The researcher used a total sampling technique. There were 26 students from IPA 3 class involved in this research. The instrument used to collect data was a written test. It was divided into pretest and post-test. The data of this research were analyzed quantitatively by using SPSS program version 20. The result of this research showed that the scrambling method effectively improves students’ grammar mastery. The mean score in the pretest is lower than the mean score in the post-test (63, 85 < 82, 23). The researcher found that the p-Value is 0.00, and the alpha is 0.05, therefore p<α (0.00 < 0.05). Meanwhile, the mean score of the post-test is better than the mean score of pretest (82,23 > 63,85).